Prognosis of Congenital Anomalies in Conceptions Following In Vitro Fertilization: A Multicenter Retrospective Cohort Study in China - Bao, Jie; Chen, Lixue; Hao, Yongxiu; Wu, Hongping; He, Xiaojin; Lu, Chuncheng; Ji, Xinhua; Qiao, Jie; Wang, Yuanyuan; Chi, Hongbin (Frontiers in Endocrinology, 2022)
Background: Conceptions following in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) have an increased risk of congenital anomalies. Few researches have explored the prognosis of fetuses with congenital anomalies. This study aimed to investigate the prevalence and prognosis of congenital anomalies in IVF/ICSI pregnancies, and to analyze the influencing factors contributing to poor prognosis. Methods: In this multicenter retrospective cohort study, we followed 405,473 embryo transfer cycles at 15 reproductive centers between January 2010 and December 2019 and enrolled 2,006 intrauterine pregnancies with congenital anomalies. The relatively positive prognosis group with one or more live births and neonatal survival for more than 7 days was compared with the poor prognosis group with poorer outcomes. Results: Among the 168,270 ongoing intrauterine pregnancy cycles, the prevalence of congenital anomalies was 1.19%. Wherein, the malformation rates of cycles with late abortion and delivery were 2.37% (716/30,202) and 0.93% (1290/138,068), respectively. Among all IVF/ICSI cycles with congenital anomalies, the relatively positive prognosis rate was 61.39%. Moreover, the fertilization failure rate (2 pro-nuclei rate <25%) in the poor prognosis group was significantly higher than that in the relatively positive prognosis group (10.89% vs. 5.09%, P <0.001). Multivariate logistic regression analysis revealed no significant differences in the relatively positive prognosis rate among the various IVF/ICSI protocols. The relatively positive prognosis rate of fertilization failure cycles was 0.180 times that of normal fertilization cycles. Conclusion: Poor fertilization rates during IVF/ICSI treatments are more likely to have poor prognosis in fetuses or neonates with congenital anomalies and obstetric management should be strengthened in pregnant women, with which the pregnant women should be recommended to strengthen obstetric management.